Venture Capital in Russia and Ukraine: Current Trends and Ways of Stepping Up Venture Investments - Krasovska, O.V. (Science and Innovation, 2024)
Venture industry in Russia and Ukraine has been analyzed from the point of view of its ability to be a source of financial support of innovation projects. Unlike the Russian venture funds the Ukrainian ones have been showed to prefer the traditional economic sectors rather than the high-techs industries. Comparative analysis of the legislative framework in Ukraine and Russia has been made.